Non Regenerative Fiber backbone Power Loss Budget - Dotche, K. A.; Banuenumah, W; Ofosu, Willie K (Discoveries in Agriculture and Food Sciences, 2016)
The most important stage in the design of a Wavelength Division Multiplexing (WDM) fiber optic system is about the choice of the correct optical transmitter, and receiver combination. This depends on the signal to be transmitted over the channel. By adopting the WDM two (2) signals at two (2) different wavelengths of 1310nm and 1550nm, can conveniently be carried on the same fiber. The WDM fiber link can carry 32,256 channels and the throughput too is high (>=2.5Gbps). Many television channels can be accommodated. The amplification along the fiber backhaul remains a bottleneck due to the non-linearity effects that could be additive. In order to minimize the non-linearity effect of the amplifiers, non-regenerative solutions are nowadays used. This paper develops a power loss budget for an optical sparse WDM long haul without inserting any regenerator along the transmission line. The study gives details of establishing a 200 km fiber optic link, operating at 2.5Gbps and supporting a digital signal of Synchronous Transport signal-48/ Synchronous Transport Module 16 (STS-48/STM-16). The link is assumed to carry 8 (WDM). In the dimensioning, the optical interfaces were chosen in agreement with the ITU-T G 654 applicable values. The system power deficit was not satisfactory in the first attempt. Then, the Erbium Doped-Fiber Amplifiers (EDFA) were inserted at the light source, and a preamplifier at the optical detector side. The system power deficit was still negative but not much. The transmitting system should have a positive value of the system power deficit so that the link budget can be suggested for the required transmission. Finally the change of the detector sensitivity gave the best estimation in the design process for the required link budget.